Design and calibration of a retarding field energy analyzer for the LTX-β scrape off layer and modeling of electrostatic potential in a collisionless SOL. (May 2019) - Zhang, X.; Elliott, D.B.; Maan, A.; Boyle, D.P.; Kaita, R.; Majeski, R.
Highlights: Li coated walls produced a collisionless scrape off layer. Ions are mirror-trapped in a collisionless scrape off layer. Ambipolar potential is significantly lower than Debye sheath potential. Potential gradient extended into the whole scrape off layer. Retarding Field Energy Analyzer successfully characterized a deuterium beam. Abstract: The Lithium Tokamak eXperiment (LTX) is a spherical tokamak device designed to study lithium plasma facing components (PFCs). The lithium coated wall of LTX has been demonstrated to produce a plasma edge with high electron temperature (200 eV or greater). Plasma density in the outer scrape-off layer (SOL) is also found to be very low, around 2 × 10 17 m -3, as a result of the low recycling lithium boundary. The high temperature, low collisionality region of the plasma extends into the SOL. The recent upgrade to LTX- β includes installation of a neutral beam, which will provide further heating and fueling of the core plasma. Core and edge diagnostics will also be expanded. As part of this expansion, a Retarding Field Energy Analyzer (RFEA) has been developed for the SOL of LTX- β . Measurements of the ion temperature, ion energy distribution, and the local space potential will be performed in the SOL plasma using this RFEA. Upgraded high field side (HFS) and low field side (LFS) Langmuir probes will replace existing triple probes so that higher electron temperatures can be more reliably measured. The HFS probes are also positioned to give radial and vertical gradient measurements. The design of the RFEA will be presented, along with calibration data. Since a high temperature, low collisional edge is expected for LTX- β, with a high mirror ratio near the LCFS (around 4), the majority of particles in the SOL will be mirror-trapped. Trapped particle effects will therefore become significant in the physics of the SOL plasma, and warrant further theoretical investigations. Here we present a theoretical study of the ambipolar potential formed in the collisionless SOL via differential loss of the electrons and ions, known as the Pastukhov potential in the literature. Numerical results will also be presented.